2020
DOI: 10.20473/jpk.v8.i2.2020.228-237
|View full text |Cite
|
Sign up to set email alerts
|

Health Promoting School Program to Prevent Hypertension of Adolescents in Indonesia and Western

Abstract: Background: Complications of hypertension causes 9.4 million of death worldwide each year. The risk factors for hypertension include heredity and environmental factors such as obesity, salt intake, physical activity, and alcohol. One-third of teenagers spent their time on school activities, so schools contribute to preventing hypertension in adolescents through Health School Program activities. Objective: to compare the health-promoting school program in Indonesia and Western in the prevention of hypertension.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…The results showed that about 81.2% of adolescents consume more than 1 tablespoon of salt per day. Unhealthy food consumption patterns such as too much salt consumption, excess carbohydrates, and fast food can be trigger factors for obesity where obesity is one of the risk factors for hypertension (Tarigan et al, 2018;Kayuningtyas & Ismayani, 2020).…”
Section: Salt Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that about 81.2% of adolescents consume more than 1 tablespoon of salt per day. Unhealthy food consumption patterns such as too much salt consumption, excess carbohydrates, and fast food can be trigger factors for obesity where obesity is one of the risk factors for hypertension (Tarigan et al, 2018;Kayuningtyas & Ismayani, 2020).…”
Section: Salt Consumptionmentioning
confidence: 99%
“…Following some research results say that low physical activity is a risk factor for hypertension. Decreased physical activity and an increasingly sedentary lifestyle may increase the risk of hypertension (Farabi et al, 2015;Ewald and Haldeman, 2016;Princewel et al, 2019;Kayuningtyas & Ismayani, 2020).…”
Section: Physical Activitymentioning
confidence: 99%